If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -1(t + 7) = 11 Reorder the terms: 3t + -1(7 + t) = 11 3t + (7 * -1 + t * -1) = 11 3t + (-7 + -1t) = 11 Reorder the terms: -7 + 3t + -1t = 11 Combine like terms: 3t + -1t = 2t -7 + 2t = 11 Solving -7 + 2t = 11 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2t = 11 + 7 Combine like terms: -7 + 7 = 0 0 + 2t = 11 + 7 2t = 11 + 7 Combine like terms: 11 + 7 = 18 2t = 18 Divide each side by '2'. t = 9 Simplifying t = 9
| 107.06=0.13x+3.06 | | 4x-6=28 | | 161+n=451 | | 6x+25-4x+25=-2 | | y=0.13(107.06)+3.06 | | 9u+4=6u+28 | | 4-1(x+1)=8 | | 4c+27=2c+57 | | (x+30)+x*2=180 | | 4-.33(x-9)=-1 | | 7y+5=3y-11 | | 4.8x+9.6=19.2 | | 3(x+5)-6x=-18 | | 169y^4-1=0 | | 4x-13+2x+19=90 | | 23+h-3.1=27 | | y=0.16(700)+17.93 | | 7x^2+(-6xy)+x+(-8)= | | x+5=4x+6 | | c=78349737+797349.3289x | | 5x-9+2x+3=90 | | 2x+16x=.40x | | 700=0.16x+17.93 | | 3x-4(9)=-19 | | 2p+7q-6(2p-9q+2r)= | | y=4(16)+45 | | 12.6-1x=2x | | 34+y=47+29 | | 3(w+7)+5w=-13 | | 16=4x+45 | | 26.25=2.75x-15 | | 132+8x=16x-12 |